The Effects of Organophosphate Esters Used as Flame Retardants and Plasticizers on Granulosa, Leydig, and Spermatogonial Cells Analyzed Using High-Content Imaging. (4th February 2022) - Wang, Xiaotong; Luu, Trang; Beal, Marc A; Barton-Maclaren, Tara S; Robaire, Bernard; Hales, Barbara F
Abstract: The replacement of regulated brominated flame retardants and plasticizers with organophosphate esters (OPEs) has led to their pervasive presence in the environment and in biological matrices. Further, there is evidence that exposure to some of these chemicals is associated with reproductive toxicity. Using a high-content imaging approach, we assessed the effects of exposure to 9 OPEs on cells related to reproductive function: KGN human granulosa cells, MA-10 mouse Leydig cells, and C18-4 mouse spermatogonial cells. The effects of OPEs were compared with those of 2, 2′, 4, 4′-tetrabromodiphenyl ether (BDE-47), a legacy brominated flame retardant. Alterations in several important cell features, including cell survival, mitochondrial dynamics, oxidative stress, lysosomes, and lipid droplets, were analyzed. Most of the OPEs tested displayed higher cytotoxicity than BDE-47 in all 3 cell lines. Effects on phenotypic parameters were specific for each cell type. Several OPEs increased total mitochondria, decreased lysosomes, increased the total area of lipid droplets, and induced oxidative stress in KGN cells; these endpoints were differentially affected in MA-10 and C18-4 cells. Alterations in cell phenotypes were highly correlated in the 2 steroidogenic cell lines for a few triaryl OPEs. Potency ranking using 2 complementary approaches, Toxicological Prioritization Index analyses and the lowest benchmark concentration/administered equivalent dose method, revealed that while most of the OPEs tested were more potent than BDE-47, others showed little to no effect. We propose that these approaches serve as lines of evidence in a screening strategy to identify the potential for reproductive and endocrine effects of emerging chemicals and assist in regulatory decision-making.